2015
DOI: 10.3390/nu7075250
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Breakfast Prior to Morning Exercise on Cognitive Performance, Mood and Appetite Later in the Day in Habitually Active Women

Abstract: Pre-exercise nutritional practices for active females exercising for mood, cognitive and appetite benefits are not well established. Results from an initial field pilot study showed that higher energy intake at breakfast was associated with lower fatigue and higher overall mood and alertness post-exercise (all p < 0.05). In a follow-up, randomised, controlled trial, 24 active women completed three trials in a balanced, cross-over design. At 0815 h participants completed baseline cognitive tasks, mood and appet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 54 publications
1
12
1
Order By: Relevance
“…In contrast to a previous postprandial exercise trial conducted in healthy, habitually active, middle-aged women, which showed an association between the consumption of breakfast and lower fatigue and higher overall mood and alertness post-exercise [16], in the present study, no relevant effect of meal intake or postprandial activity behavior on the measured mood dimensions (good vs. bad mood, alertness vs. fatigue, and ease vs. unease) could be observed (Table 4). Despite statistical significance, for all three dimensions, changes in mean values between all time points were minor.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…In contrast to a previous postprandial exercise trial conducted in healthy, habitually active, middle-aged women, which showed an association between the consumption of breakfast and lower fatigue and higher overall mood and alertness post-exercise [16], in the present study, no relevant effect of meal intake or postprandial activity behavior on the measured mood dimensions (good vs. bad mood, alertness vs. fatigue, and ease vs. unease) could be observed (Table 4). Despite statistical significance, for all three dimensions, changes in mean values between all time points were minor.…”
Section: Discussioncontrasting
confidence: 59%
“…Current randomized interventions trials evaluating the acute interactive effects of meal composition and physical activity on cognitive performance and emotions are limited [15,16] and to the best of our knowledge, no previous human study has investigated the acute effects of postprandial exercise suitable for daily implementation neither on postprandial attention as a complex cognitive function, nor on mood/emotions following the consumption of meals reflecting different dietary patterns, especially in subjects with a risk phenotype for the development of cardiovascular and neurodegenerative diseases (e.g., elevated age; characteristics of metabolic syndrome). Since current research suggests that breakfast as the first meal of the day is most important from a dietary perspective [17] and is vital for optimal cognitive function and intellectual performance by providing readily available energy to the brain [18], the test meals in the present study were provided as breakfast challenges after an overnight fast (≥12 h).…”
Section: Introductionmentioning
confidence: 99%
“…there was no difference between baseline and 2.5-h). Breakfast consumption has been shown to both improve [37, 38] and worsen [39] cognitive function. Subsequently, future studies should consider the effects of the inclusion and composition of breakfast on cognitive performance [39] and whether this could affect cognitive responses to breaking up prolonged sitting.…”
Section: Discussionmentioning
confidence: 99%
“…Morning training sessions are common place for both athletes and recreational exercisers, and many athletes report skipping breakfast in the morning (33,35). Therefore, it is likely that at least some training will take place in a fasted state, where glycogen levels (at least liver glycogen) will be suboptimal.…”
mentioning
confidence: 99%